Rewritable multi-event analog recording in bacterial and mammalian cells - Tang, Weixin; Liu, David R. (Science (American Association for the Advancement of Science), 2018)
Recording cellular events could advance our understanding of cellular history and responses to stimuli. The construction of intracellular memory devices, however, is challenging. Tang and Liu used Cas9 nucleases and base editors to record amplitude, duration, and order of stimuli as stable changes in both genomic and extrachromosomal DNA content (see the Perspective by Ho and Bennett). The recording of multiple stimuli—including exposure to antibiotics, nutrients, viruses, and light, as well as Wnt signaling—was achieved in living bacterial and human cells. Recorded memories could be erased and re-recorded over multiple cycles. Science , this issue p. eaap8992 ; see also p. 150 Base editors and CRISPR nucleases generate “cell data recorders” that enable durable, analog, rewritable recording of multiple stimuli. We present two CRISPR-mediated analog multi-event recording apparatus (CAMERA) systems that use base editors and Cas9 nucleases to record cellular events in bacteria and mammalian cells. The devices record signal amplitude or duration as changes in the ratio of mutually exclusive DNA sequences (CAMERA 1) or as single-base modifications (CAMERA 2). We achieved recording of multiple stimuli in bacteria or mammalian cells, including exposure to antibiotics, nutrients, viruses, light, and changes in Wnt signaling. When recording to multicopy plasmids, reliable readout requires as few as 10 to 100 cells. The order of stimuli can be recorded through an overlapping guide RNA design, and memories can be erased and re-recorded over multiple cycles. CAMERA systems serve as “cell data recorders” that write a history of endogenous or exogenous signaling events into permanent DNA sequence modifications in living cells.